2005
DOI: 10.1007/s00296-004-0539-9
|View full text |Cite
|
Sign up to set email alerts
|

The −590 IL-4 promoter polymorphism in patients with rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory disease in which cytokines play an important role. The aim of the present study was to evaluate the -590 IL-4 promoter polymorphism in patients with RA and its association with disease activity and severity. We enrolled 94 patients with RA diagnosed according to the criteria of the American College of Rheumatology. Polymerase chain reaction amplification was used for analysis of the polymorphism at position -590 of the promoter of the IL-4 gene. The distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 18 publications
2
38
0
3
Order By: Relevance
“…[6][7][8][9][10][11] Screening of this SNP in 869 MS patients and 595 controls demonstrated this sequence variation to be associated with MS (see Table 1). Genotyping of two flanking SNPs (rs2243248 and rs2070874) revealed that exclusively the À589 C allele is associated with MS (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11] Screening of this SNP in 869 MS patients and 595 controls demonstrated this sequence variation to be associated with MS (see Table 1). Genotyping of two flanking SNPs (rs2243248 and rs2070874) revealed that exclusively the À589 C allele is associated with MS (see Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…4 Usually, IL4 is secreted by lymphocytes of the Th2 lineage, 5 whereas the IL4 locus appears silenced in Th1 cells. Because of its immune response regulating role, IL4 is an obvious candidate gene for potential association in MS. We focus here on the IL4 promoter polymorphism À589C/T, since numerous studies have shown association of this single nucleotide polymorphism (SNP) with various inflammatory diseases, including asthma, atopy, brucellosis and rheumatoid arthritis, [6][7][8][9][10][11] and because earlier deletion expression assays hinted to a functional role of this SNP. 12 Genotyping two neighbouring polymorphisms revealed that exclusively SNP À589 C/T is associated significantly with MS.…”
Section: Introductionmentioning
confidence: 99%
“…Carriers of T allele were significantly more likely to have positive anti-CCP [51] . The same polymorphism was tested in a Polish RA population, where no significant differences were observed in the genotype and allele frequencies of controls vs RA patients [52] . Meta-analysis showed that the -590 C/T polymorphism is a risk factor for RA among Europeans [53] .…”
Section: The Il-2 Familymentioning
confidence: 99%
“…Also, Pawlik et al,found that the IL-4R I50V variant has been associated with increased radiological damage during the first 2 years of disease [45], while Marinou et al, failed to support such associations in an English population [46].Burgos et al,also, failed to support such associations in an African American population. Perhaps this effect was not observed due to the different racial/ethnic composition of the patients studied [47].…”
Section: Discussionmentioning
confidence: 89%